Cases of hemorrhagic fever with renal syndrome caused by hantavirus in the Kharkiv region among military personnel - E.M. Khoroshun; K.I. Bodnia; L.V. Zavgorodnia; І.M. Asoyan; P.V. Nartov; V.V. Nehoduiko; V.V. Kondratyuk (Медицина неотложных состояний)
The military personnel’s stay in the field, in places of natural hantavirus foci in the Kharkiv region, and contact with rodents led to the development of hemorrhagic fever with renal syndrome. Serologic testing for IgM and IgG to hantaviruses revealed the Puumala serotype in all 11 patients. The main complaints were fever, general weakness, headache, low back pain, muscle pain, decreased urine output and quantity. An objective examination revealed an enlarged liver and a positive Pasternacki’s symptom. All participants had erythrocytosis and thrombocytopenia. Patients also had increased levels of alanine aminotransferase, creatinine and urea, C-reactive protein, chloride and sodium in the blood. In critically ill patients, there were changes in blood coagulation parameters: an increase in activated partial thromboplastin time, fibrinogen and a decrease in prothrombin time. Ultrasound examination revealed diffuse changes in the liver parenchyma and inflammatory kidney damage. The comprehensive therapy contributed to the recovery of all the soldiers.